Optimal Overhaul-Replacement Policies for Repairable Machine Sold with Warranty - Soemadi, Kusmaningrum; Iskandar, Bermawi P.; Taroepratjeka, Harsono (ITB Journal Publisher, LPPM ITB, 2014)
This research deals with an overhaul-replacement policy for a repairable machine sold with Free Replacement Warranty (FRW). The machine will be used for a finite horizon, T (T <ï¥), and evaluated at a fixed interval, s (s< T). At each evaluation point, the buyer considers three alternative decisions i.e. Keep the machine, Overhaul it, or Replace it with a new identical one. An overhaul can reduce the machine age virtually, but not to a point that the machine is as good as new. If the machine fails during the warranty period, it is rectified at no cost to the buyer. Any failure occurring before and after the expiry of the warranty is restored by minimal repair. An overhaul-replacement policy is formulated for such machines by using dynamic programming approach to obtain the buyerâs optimal policy. The results show that a significant rejuvenation effect due to overhaul may extend the length of machine life cycle and delay the replacement decision. In contrast, the warranty stimulates early machine replacement and by then increases the replacement frequencies for a certain range of replacement cost. This demonstrates that to minimize the total ownership cost over T the buyer needs to consider the minimal repair cost reduction due to rejuvenation effect of overhaul as well as the warranty benefit due to replacement. Numerical examples are presented for both illustrating the optimal policy and describing the behavior of the optimal solution.